Residual stress and microstructure depth gradients in nitrided iron-based alloys revealed by dynamical cross-sectional transmission X-ray microdiffraction. (1st April 2015) - Kurz, S.J.B.; Meka, S.R.; Schell, N.; Ecker, W.; Keckes, J.; Mittemeijer, E.J.
Abstract: Thermochemical surface treatments such as nitriding result in the formation of complex near-surface gradients of phase fractions, residual stress and microstructure, which influence the structural and functional properties of the material decisively. In this work, a novel cross-sectional synchrotron microdiffraction method is used to characterize such gradients by analyzing cross-sections of nitrided Fe–Al and Fe–V alloy specimens down to a depth of 500 μm, with a depth resolution of less than 10 μm. The Debye–Scherrer diffraction data collected from the individual sample depths document very different nitride-precipitation mechanisms and resulting stress gradients. In nitrided Fe–Al samples, the delayed precipitation of largely incoherent AlN particles leads initially to the development of internal microcracks, followed by a pronounced increase of compressive stress until plastic deformation sets in, which finally results in the formation of regions with tensile and compressive stress. In contrast, the VN precipitation during nitriding of Fe–V alloys occurs very quickly and generates a desired high compressive stress at the surface of the nitrided part. The tiny and coherent VN precipitates increase the yield strength of the nitrided zone significantly. The evaluated corresponding ferrite-lattice parameter depth profiles can be quantitatively described as the outcome of (competing) effects of solute (Al, V) depletion, (excess) nitrogen dissolution and the emergence of a hydrostatic strain due to elastic accommodation of the precipitate/matrix misfit. The novel technique to expose depth gradients in real space, with micrometer resolution, opens the way to understand the development of microstructure and stress upon (thermochemical) surface treatment.